Meningkatkan Aktivitas Keterampilan Berpikir Kritis Dan Kolaborasi Menggunakan Model Problem Based Learning Dibantu Dengan Model Dnmp Serta Permainan Ular Tangga Di Kelas IV SDN Kelayan Selatan 8 - Nizmatullayla; Zain Ahmad Fauzi (CV. ITTC INDONESIA, 2023)
This research was conducted because the background is the problem of students who do not participate actively in learning activities that have a negative impact on collaboration abilities and skills in critical thinking. So the use of a problem based learning model supported by the DNMP model of the Snakes and Ladders game is a way to overcome the problems mentioned above. Theme 7: The Beauty of Bhinnekaku in My Country is the subject of research, with the aim of further describing the activities of teachers, students, skills in critical thinking, collaboration between fourth grade students. This research utilizes PTK which is completed in 2 meetings. Fifteen grade IV students at SDN Kelayan Selatan 8 were used as the subjects of this study. The information taken is subjective information obtained through paying attention to teacher training, student training and decisive critical thinking skills and coordinated efforts. As well as quantitative information for student learning outcomes obtained through tests. The fact that 80% of students achieve KKM scores of less than 80 is a sign of successful research with learning mastery. The consequences of this study showed that there was an increase in teacher activity in cycles I and II from 17 to 19. Student activity from 73% to 86% in the second cycle. Critical thinking skills become 92%. Collaboration skills become 93% and learning outcomes become 100% in cycle II.